An investigation into cohesive devices in IELTS reading texts - Nguyễn,Thị Thúy Ngân; Nguyễn Thị Quỳnh Hoa, Ph.D. (Đà Nẵng : The University of Da Nang, 2015)
Cohesive devices are one of the linguistic factors which are used to express the ties between the cohered parts in a discourse. Cohesive devices play an important role in linking ideas of the text, therefore a deep understanding of cohesive devices help readers improve their reading skills. Based on the theory of Halliday and Hasan, this thesis mainly aims at examining the common types of cohesive devices, syntactic and semantic features of cohesive devices in IELTS Reading Texts. The data of the study, 217 samples were collected from five IELTS official Practice Test books published by Cambridge University Press from 2010 to 2015. The data are quoted, described and analyzed in terms of Reading Passages 1 on syntactic and semantic aspects under qualitative and quantitative approaches. The thesis attempts to figure out some commonly used types of cohesive devices in IELTS Reading texts. They are grammatical cohesive devices and lexical cohesive devices. The former consist of reference, substitution, ellipsis, conjunction and the latter are reiteration and collocation. The syntactic features help the readers realize cohesive devices. The semantic features help readers understand the texts. The findings also aims at suggesting some implications for learning and teaching English as a foreign language, especially to better the awareness of learners and test takers in understanding and doing IELTS reading tests.
Master thesis in social sciences and humanities.
Includes references (p. 100-104).
Keywords: cohesive devices in IELTS reading texts; The English language; cohesive devices -- IELTS reading texts